Sometimes people march - Allen, Tessa (New York, NY : Balzer + Bray, 2020)
Combines rudimentary facts about peaceful resistance with art that depicts organized actions from the 19th century through today, and endnotes reveal more specifics about each illustration, including historic figures represented.
2.6
K-3
AD960L
Some copies purchased with funds from CPSF Equity Grant - 2022.
Keywords: Civil disobedience -- Juvenile literature; Demonstrations -- Juvenile literature; Civil disobedience; Demonstrations; Nonfiction picture books; Human rights